Analisis Kebutuhan Media Pembelajaran Interaktif Berbasis PowerPoint pada Materi Pecahan pada Siswa Kelas V SD - Alfi Rokhmatin; Sita Isna Malyuna; Sumadi Sumadi (FONDATIA, 2026)
This study was motivated by the suboptimal use of interactive learning media in mathematics learning at the elementary school level, particularly in fraction material, which is abstract and therefore difficult for students to understand. This study aimed to analyze the learning process, students’ level of understanding, and students’ needs for the development of PowerPoint-based interactive learning media on fraction material in fifth-grade elementary school. This study used a quantitative approach with a descriptive method. The research sample consisted of eight students selected using purposive sampling. Data were collected through a closed-ended questionnaire based on a Likert scale and were then analyzed descriptively and quantitatively using percentages. The results showed that the learning process was in the high to very high category, but some students still experienced difficulties in understanding fraction material. In addition, the need for PowerPoint-based interactive learning media was in the very high category, with the majority of students, at 87.5%, showing a strong need for more engaging and interactive media. The conclusion of this study confirms that the development of PowerPoint-based interactive learning media is highly needed to help improve students’ understanding of fraction concepts and their engagement in learning. The implications of this study theoretically enrich studies on digital learning media in elementary schools, while practically providing recommendations for teachers to develop innovative, visual, and interactive learning media to improve the quality of mathematics learning.